MEREKONTRUKSI BALE SIPON MENJADI “LITTLE UBUD” : Potensi Dan Peluang Pengembangannya - Yoyok Antoni; Ayu Gardenia Lantang (Universitas Mataram, 2026)
The purpose of this research was to determine the potential and opportunities of Bale Sipon as an alternative